2006
DOI: 10.1002/micr.20243
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral plasticity in crossed C7 grafts of the brachial plexus: An fMRI study

Abstract: In order to rescue elbow flexion after complete accidental avulsion of one brachial plexus, seven patients underwent a neurotization of the biceps with fibers from the contralateral C7 root. The C7 fibers used for the graft belonged to the pyramidal pathway, which descends from the cerebral hemisphere ipsilateral to the damaged plexus, and which controls extension and abduction of the contralateral arm. After several months of reeducation, a functional magentic resonance imaging study was performed with a 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 19 publications
2
40
0
1
Order By: Relevance
“…18,[31][32][33][34][35][36][37] Clinically, an fMRI study on neurotization of the biceps with the contralateral C7 root showed that flexion of the neurotized arm was associated with a bilateral network activity. 18 The contralateral cortex that originally involved in control of the repaired arm still participated in the elaboration and control of the task through the bilateral premotor and primary motor cortex. 18 In this study, we transferred the contralateral C7 root to the median nerve to restore the function of forepaw flexion in rats.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…18,[31][32][33][34][35][36][37] Clinically, an fMRI study on neurotization of the biceps with the contralateral C7 root showed that flexion of the neurotized arm was associated with a bilateral network activity. 18 The contralateral cortex that originally involved in control of the repaired arm still participated in the elaboration and control of the task through the bilateral premotor and primary motor cortex. 18 In this study, we transferred the contralateral C7 root to the median nerve to restore the function of forepaw flexion in rats.…”
Section: Discussionmentioning
confidence: 98%
“…18 The contralateral cortex that originally involved in control of the repaired arm still participated in the elaboration and control of the task through the bilateral premotor and primary motor cortex. 18 In this study, we transferred the contralateral C7 root to the median nerve to restore the function of forepaw flexion in rats. The results showed that the injured forepaw representation area was found in the ipsilateral motor cortex 5 months after the nerve transfer of contralateral C7 root, which proved that both the left injured limb and the right healthy limb were controlled by the left motor cortex simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The original motor area for flexion of the arm is still involved but in concert with the ipsilateral cortex, which normally is not the case (Fig. 6).…”
Section: Contralateral C-7 Transfermentioning
confidence: 96%
“…Al igual que el "brazo que respira" descrito para el nervio frénico, el movimiento sincrónico del lado sano es necesario típicamente al comienzo del proceso de reinervación para obtener una contracción muscular en el lado afectado. Más tarde, como regla general, se consigue un control mayor, aunque no totalmente independiente 4 . Estos resultados limitados, junto con el bajo, aunque no inexistente riesgo de déficit sensitivo o motor (lo que no es un problema menor en el contexto de un paciente con una sola extremidad superior normal), el mencionado fenómeno de cocontracción del brazo sano, y la complejidad técnica de este procedimiento, se opuso a su uso generalizado y su indicación queda limitada a ciertos pacientes muy seleccionados con lesiones concomitantes de nervio frénico y espinal accesorio.…”
Section: Transferencia De La Raíz C7 Contralateralunclassified